EDUCATION FOR MENTALLY RETARDED CHILDREN IN A FAMILY WITH AN ISLAMIC EDUCATION PERSPECTIVE - Elly Damaiwati; Kumaidi Kumaidi; Musa Asy’arie (Profetika: Jurnal Studi Islam, 2022)
Mental retardation is a condition of children whose intelligence is far below the average and is characterized by limited intelligence and incompetence in social communication. Islam views children with mental retardation as entities that must be considered for several strong reasons. The most basic is in the name of humanity. One fact that cannot be forgotten is that they are both creatures of God who must be respected. Moreover, the mentally retarded child is also a human being glorified by God. Mentally retarded children also have the same degree and social status as normal children, so in Islamic education, there should be no inequality in obtaining the right to education. This study aims to determine that the family is the most important factor in the education of mentally retarded children. This research is naturalistic qualitative. Documentation, observation, and interviews are the methods used to collect data. The data analysis uses data reduction, data presentation, and verification. The results of this study indicate that the family becomes a model and habituation of good behavior in everyday life as a positive strategy for the education of mentally retarded children, The family also applies several pillars, one of which is the aspect of faith, the aspect of worship and the moral aspect as the basis for educating their children.